Systems, software and services process improvement : 24th European Conference, EuroSPI 2017, Ostrava, Czech Republic, September 6-8, 2017, Proceedings /: 24th European Conference, EuroSPI 2017, Ostrava, Czech Republic, September 6-8, 2017, Proceedings. (2017) - Unknown
No abstract available